2009
DOI: 10.1038/bmt.2009.128
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome after allo-SCT: close follow-up on a large cohort treated with myeloablative regimens

Abstract: We analyzed the late outcomes of 429 long-term survivors post allogeneic hematopoietic SCT (allo-HSCT) who received transplant in our center between 1981 and 2002, and were free of their primary disease for X2 years after allo-HSCT. Late recurrent primary malignancy was found in 58 (13.5%) patients and was the primary cause of late death. A total of 37 (8.6%) patients died of nonrelapse causes at a median of 5.5 years (range, 2-15.6 years) post allo-HSCT. The major non-relapse causes of death were chronic GVHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 34 publications
(34 reference statements)
1
63
0
2
Order By: Relevance
“…15 Similarly, numerous other studies in adults have demonstrated that chronic GVHD is a significant risk factor and a major cause of late mortality regardless of infectious complications. 1,3,16,17 As chronic GVHD is less prevalent in children, we observed lower rates of death due to chronic GVHD (only 1.2%) and infections (2.2%) compared with the adult literature. 1,3,4 However, it has been shown that once chronic GVHD occurs, 5 year OS is only 60%.…”
Section: Study Populationmentioning
confidence: 49%
See 1 more Smart Citation
“…15 Similarly, numerous other studies in adults have demonstrated that chronic GVHD is a significant risk factor and a major cause of late mortality regardless of infectious complications. 1,3,16,17 As chronic GVHD is less prevalent in children, we observed lower rates of death due to chronic GVHD (only 1.2%) and infections (2.2%) compared with the adult literature. 1,3,4 However, it has been shown that once chronic GVHD occurs, 5 year OS is only 60%.…”
Section: Study Populationmentioning
confidence: 49%
“…18 Second malignant neoplasms have also been demonstrated to be a significant cause of late mortality in adults. 1,16 Survivors of allogeneic HSCT have been shown to be at a 12-fold increased risk of developing another malignancy when compared with the general population. 12 Although the risk for the development of a second malignant neoplasm increases with increasing time from HSCT, we did not find new malignancies to be a major cause of late mortality despite a median follow-up of 10.0 years.…”
Section: Study Populationmentioning
confidence: 99%
“…Because these practices are relatively new, their impact on risk for SN is poorly understood. Most studies have shown no association, 22,36,38,41 but they are generally small with limited follow-up.…”
Section: Disease- and Transplant-related Risk Factorsmentioning
confidence: 99%
“…17 Among 28,874 patients undergoing allogeneic HCT, those transplanted for chronic myelogenous leukemia (CML) had a lower risk of solid cancers than patients with acute leukemia, 39 but this has not been confirmed in other studies. 37,38 Two studies reported increased SN risks with more advanced disease, including adults with lymphoid malignances undergoing autologous HCT (N=300) 59 and patients with FA undergoing allogeneic HCT (N=795). 69 However, disease status was not associated with SN risk in 1487 pediatric autologous HCT recipients with a variety of primary diagnoses.…”
Section: Disease- and Transplant-related Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation